PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KEBIJAKAN HUTANG DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Vivi Hendryani; Muhammad Nuryatno Amin (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2022)
The purpose of this study is to test, analyze and prove empirically whether firm size, profitability, debt policy and dividend policy have an effect on firm value. This study uses multiple linear regression analysis. The research population is Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2015 to 2019. The data source is secondary data, the data needed is through www.idx.co.id. The sampling technique of this research is purposive sampling. The method of data analysis is to analyze multiple linear regression. The time span of this research uses panel data. The results showed that firm size, profitability and debt policy had a positive effect on firm value. Dividend policy has no effect on firm value